Detection of sarcocyst in meat from local markets in Selangor: highlighting the use of crude sample in PCR / Azdayanti Muslim … [et al.] - Muslim, Azdayanti (Faculty of Medicine, 2016)
Sarcocystis spp. are obligate intracellular protozoan parasites which cause meat-borne parasitic disease. In Malaysia, sarcocystosis is seen as a potential emerging food-borne zoonosis after a series of large outbreak of human infections. Humans acquire infection either by ingestion of cyst in raw or undercooked infected meat or from sporocysts in contaminated food and water. The goal of this study is to identify the presence of sarcocystis parasites in meat of cattle, buffaloes, sheep and goats collected from local markets in Selangor, Malaysia. Methods: A total of 64 skeletal muscles samples (57 cattle, 2 buffaloes, 4 goats and 1 sheep) were collected from local markets. The samples were cut randomly into three pieces, squashed firmly between two glass slides and then examined microscopically for the presence of cysts. Results: Three samples of meat (4.69 %) from cattle (1), buffalo (1) and sheep (1) were found to be positive for cysts. The cysts were confirmed by PCR as sarcocystis sp.